Biomechanical Consequences of Nail Insertion Point and Anterior Cortical Perforation for Antegrade Femoral Nailing. (18th December 2020) - Ching, Michael; Gee, Aaron; Del Balso, Christopher; Lawendy, Abdel; Schemitsch, Emil H.; Zdero, Radovan; Sanders, David
Abstract : This biomechanical study assessed the influence of changing antegrade cephalomedullary nail insertion point from anterior to neutral to posterior locations relative to the tip of the greater trochanter with or without anterior cortical perforation in the distal femur. Artificial osteoporotic femurs and cephalomedullary nails were used to create 5 test groups each with 8 specimens: intact femur without a nail or perforation, anterior nail insertion point without perforation, neutral nail insertion point without perforation, posterior nail insertion point without perforation, and posterior nail insertion point with perforation. Nondestructive biomechanical tests were done at 250 N in axial, coronal 3-point bending, sagittal 3-point bending, and torsional loading in order to measure overall stiffness and bone stress. The intact femur group vs. all femur/nail groups had lower stiffness in all loading modes (p ≤ 0.018 ), as well as higher bone stress in the proximal femur (p ≤ 0.027 ) but not in the distal femur above the perforation (p = 0.096 ). Compared to each other, femur/nail groups only showed differences in sagittal 3-point bending stiffness for anterior and neutral vs. posterior nail insertion points without (p ≤ 0.025 ) and with perforation (p ≤ 0.047 ). Although it did not achieve statistical significance (p ≥ 0.096 ), moving the nail insertion point from anterior to neutral to posterior to posterior with perforation did gradually increase bone stress by 45% (proximal femur) and 46% (distal femur). No femur or hardware failures occurred. Moving the nail insertion point and the presence of a perforation had little effect on stiffness, but the increased bone stress may be important as a predictor of fracture. Based on current bone stress results, surgeons should use anterior or neutral nail insertion points to reduce the risk of anterior cortical perforation.